Dental Stem Cell-Derived Exosomes: A Review of Their Isolation, Classification, Functions, and Mechanisms - Xiner Ning; Rui Liu; Yingying Huang; Zhilong Huang; Haodi Li; Qiqi Li; Zengyan Sheng; Junjie Wu (Wiley, 2024)
The scientific field concerned with the study of regeneration has developed rapidly in recent years. Stem cell therapy is a highly promising therapeutic modality for repairing tissue defects; however, several limitations exist, such as cytotoxicity, potential immune rejection, and ethical issues. Exosomes secreted by stem cells are cell-specific secreted vesicles that play a regulatory role in many biological functions in the human body; they not only have a series of functional roles of stem cells and exert the expected therapeutic effects, but they can also overcome the mass limitations of stem cells and are thus considered in the research as an alternative treatment strategy for stem cells. Since dental stem cell-derived exosomes (DSC-Exos) are easy to acquire and present modulating effects in several fields, including neurovascular regeneration and craniofacial soft and hard tissue regeneration processes, they are served as an emerging cell-free therapeutic strategy in various systematic diseases. There is a growing body of research on various types of DSC-Exos; however, they lack systematic elaboration and tabular summarization. Therefore, this review presents the isolation, characterization, and phenotypes of DSC-Exos and focuses on their current status of functions and mechanisms, as well as the multiple challenges prior to clinical applications.